Implementation of Problem Based Learning (PBL) Electronic Module Teaching Materials to Increase Student Interest and Learning Outcomes in Reaction Rate Material - Siregar, Raudatul Hasanah; Rosita, Linda; Jwitaningsih, Tita (Universitas Lampung, 2024)
This implementation research is to determine the comparison of the improvement of learning outcomes and interest of students taught by using electronic module teaching materials based on Problem Based Learning and students taught by using high school chemistry textbook teaching materials and to determine the relationship between interest and the improvement of student learning outcomes in reaction rate material class XI at SMA Negeri 14 Medan. This research is a pure experimental research with pretest-posttest control group desaign design. Samples in the study were taken 2 classes using random sampling technique, namely class XI IPA 5 as an experimental class taught using PBL-based electronic module teaching materials and class XI IPA 2 as a control class taught using high school chemistry textbook teaching materials. The application of electronic module teaching materials is measured through the difference in the average n-Gain of student learning outcomes and interest, both in the experimental and control classes. The results showed that the increase in student learning outcomes and interest in the experimental class was higher than in the control class. The average increase in learning outcomes in the experimental class was 0.71 with an increase in interest of 0.54 and an increase in learning outcomes in the control class was 0.478 with an increase in interest of 0.31. Then, there is a correlation between interest and the improvement of student learning outcomes taught using PBL-based electronic module teaching materials of 0.764 with a high category.Keywords: PBL-based electronic modules, learning outcomes, learning interestDOI: 10.23960/jppk.v13.i1.2024.06